2022
DOI: 10.1038/s41598-022-21985-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of executive functions, social cognition and intelligence in predicting social adaptation of vulnerable populations

Abstract: This study sought to evaluate the roles of and interactions between cognitive processes that have been shown to exhibit impact from socioeconomic status (SES) and living conditions in predicting social adaptation (SA) in a population of adults living in socially vulnerable conditions. Participants included 226 people between the ages of 18 and 60 who have been living in vulnerable contexts throughout life in Santiago, Chile. Data was collected through a battery of psychological assessments. A structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
1
5
0
1
Order By: Relevance
“…Cognitive control and social cognition are core aspects of social adaptation ( Huepe et al, 2011 ; Samadi and Sohrabi, 2016 ; Neely-Prado et al, 2019 ). This is consistent with recent conceptualizations of social adaptation as a dynamic process encompassing the accommodation own thoughts and behaviors based on social norms and expectations ( Londono and McMillan, 2015 ; Neely-Prado et al, 2021 ; Schulte et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cognitive control and social cognition are core aspects of social adaptation ( Huepe et al, 2011 ; Samadi and Sohrabi, 2016 ; Neely-Prado et al, 2019 ). This is consistent with recent conceptualizations of social adaptation as a dynamic process encompassing the accommodation own thoughts and behaviors based on social norms and expectations ( Londono and McMillan, 2015 ; Neely-Prado et al, 2021 ; Schulte et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Loneliness is associated with increased depressive symptoms due to dysfunctional cognition, self-regulation ( Tong et al, 2021 ; Steen et al, 2022 ), alterations in white matter (WM) structures associated with social cognition ( Nakagawa et al, 2015 ) and cognitive control ( Lam et al, 2021 ). However, the negative impact of loneliness can be minimized by social adaptation, defined as appropriate social functioning in line with social norms and expectations ( Londono and McMillan, 2015 ; Neely-Prado et al, 2021 ; Schulte et al, 2022 ). Social adaptation can reduce depressive symptoms through increased social support ( Berkman and Glass, 2000 ; Heinrichs et al, 2003 ; Cohen, 2020 ), enhanced self-esteem ( Denissen et al, 2008 ; Joseph and De Guzman, 2021 ), exposure to stimulating environments ( Jopp and Hertzog, 2010 ; Stevens et al, 2021 ), and enhancement of cognitive and brain reserve ( Darwish et al, 2018 ; Zhao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies have shown neural strategies for self-other distinction, which is a critical mechanism to distinguish between our experience and that of others ( Decety, 2020 ). Based on this neuroscientific framework, the neural basis of empathy has been essential in understanding social cognition in clinical populations ( Smith, 2009 ; Derntl et al, 2012 ), people with social vulnerability ( Schulte et al, 2022 ), healthcare professionals ( Decety, 2020 ), as well as the use of empathy training in the general population ( Klimecki et al, 2014 ), and social interventions in educational and health contexts ( Smith et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, their social adaptation (SA) is hindered (Schulte et al, 2022). The cumulative number and intensity of stressors experienced by these individuals, coupled with their inadequate access to stress management resources, contribute to conditions that are conducive to poor mental health and chronic stress (Evans & France, 2022;Evans & Kim, 2010).…”
Section: Introductionmentioning
confidence: 99%